Describe the Motivation and Learning Outcomes of Grade Sixth Students of SD Inpres 2 Lasoani on Science Learning through the use of Science Kit SEQIP Model. - Saleh, Saleh; Tellu, Andi Tanra; Darsikin, Darsikin (Universitas Tadulako, 2017)
The purpose of this study is to describe the motivation and learning outcomes of grade sixth students of SD Inpres 2 Lasoani on science learning through the use of science Kit SEQIP model. The method used is classroom action research method with two cycles. Each cycle consists of two meetings. The result of the first meeting at the first cycle are that the observation on activity of students scored 68%, are in the category enough, the student's classical absorption rate of 72%, students' classical completeness 47% and student learning motivation 62% are in enough category. The result of the second meeting at the first cycle are that activity of students scored 78%, is in good category, students' classical absorbency 79%, student's 72% classical learning completeness and 75% student learning motivation are in good category. The result of the first meeting at the second cycle are that the observation on activity of students scored 80% value, is in good category, students' absorbency 83%, student 89% classical learning completeness and student learning motivation 82% are in good category. The result of the second meeting at the second cycle are that the observation on activity of students scored 91% value, is in very good category, classical student absorbency 89%, 97% student learning completeness and student learning motivation 92% are in very good category. In conclusion the use of science Kit SEQIP model on science learning can improve the motivation and learning outcomes of students in grade sixth SD Inpres 2 Lasoani.